Oxford English for computing - Boeckner, Keith (Oxford University Press, 1993)
A course for people studying computer science or working with computers. It covers a wide range of computing areas, giving practice in all four language skills. Particular emphasis is placed on the vocabulary and grammar of the English used in computer science